2014
DOI: 10.1103/physreva.89.034303
|View full text |Cite
|
Sign up to set email alerts
|

Monogamy of entanglement of formation

Abstract: It is well known that a particle cannot freely share entanglement with two or more particles. This restriction is generally called monogamy. However the formal quantification of such restriction is only known for some measures of entanglement and for two-level systems. The first and broadly known monogamy relation was established by Coffman, Kundu, and Wootters for the square of the concurrence. Since then, it is usually said that the entanglement of formation is not monogamous, as it does not obey the same re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 18 publications
(35 reference statements)
1
83
0
Order By: Relevance
“…Such monogamy relations are not always satisfied by entanglement measures. Although the concurrence C and entanglement of formation E do not satisfy such monogamy inequality, it has been shown that the squared concurrence C 2 [9,10] and the squared entanglement of formation E 2 [11] do satisfy the monogamy relations. In this paper, we study the general monogamy inequalities satisfied by the αth power of concurrence C α and the αth power of entanglement of formation E α .…”
Section: Introductionmentioning
confidence: 99%
“…Such monogamy relations are not always satisfied by entanglement measures. Although the concurrence C and entanglement of formation E do not satisfy such monogamy inequality, it has been shown that the squared concurrence C 2 [9,10] and the squared entanglement of formation E 2 [11] do satisfy the monogamy relations. In this paper, we study the general monogamy inequalities satisfied by the αth power of concurrence C α and the αth power of entanglement of formation E α .…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists a kind of three-qubit mixed states which is entangled but without two-qubit concurrence and three-tangle [38], and the similar case also exists in Nqubit systems [39]. Recently, it was indicated that the squared entanglement of formation (SEF) [3] obeys the monogamy relation in multiqubit systems [40][41][42][43][44][45]. In particular, it was which overcomes the flaw of the MoE of SC and can be utilized to detect all multiqubit entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…The higher power, the graph is nearer to the vertical axis. It has been found that several measures of quantum correlations like squared concurrence [24,25], squared negativity [66][67][68], squared quantum discord [36], global quantum discord [69,70], squared entanglement of formation [71,72], Bell inequality [73][74][75], EPR steering [76,77], contextual inequalities [78,79], etc. exhibit monogamy property.…”
Section: Introductionmentioning
confidence: 99%